Core overview images of IODP Hole 389-M0096C - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Collection of core overview image reports from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Core overview images reports for each core are automatically produced by the mDIS (mobile Drilling Information System) using the archive half line scan image of available sections once uploaded to the systems extquotesingle file management. Line scan images were obtained during the onshore phase from the cleaned fresh cut surfaces directly after longitudinal splitting of core sections into work and archive halves. For production of core overview reports the curated cropped images of the respective archive halves were used. File naming follows standard IODP file naming convention: Exp-SiteHole-CoreCoretype. For example, a file 389-M0109A-06R.pdf identifies the report for core 6R (R indicating rotary coring method), from Hole M0109A from Expedition 389. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025